2020
DOI: 10.5658/wood.2020.48.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rice Straw, Bagasse, and their Combination on the Properties of Binderless Particleboard

Abstract: In this study, rice straw and bagasse are used as raw materials to produce binderless particleboard (BPB). This study aims to evaluate the mechanical and physical properties of BPB. We identify the raw material that would be better for the production of BPB from the viewpoint of their basic properties. The BPBs are made from rice straw, bagasse, and combinations of both in ratios of 50:50 and 40:60, respectively. The modulus of elasticity (MOE), modulus of rupture (MOR), internal bonding (IB) strength, water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The material with the highest mechanical properties in this study was prepared with only fine particles, with a flexural modulus of 6.9 GPa and a flexural strength of 43.6 MPa. In comparison, other studies on manufacturing binderless materials from bagasse reported much lower mechanical properties (flexural modulus < 2 GPa and flexural strength < 20 MPa) [23,26,50,66]. Meanwhile, the material with the highest water resistance was prepared with a 30 min molding time, giving a WA of 21% and a TS of 9%.…”
Section: Choice Of Best Conditionsmentioning
confidence: 91%
“…The material with the highest mechanical properties in this study was prepared with only fine particles, with a flexural modulus of 6.9 GPa and a flexural strength of 43.6 MPa. In comparison, other studies on manufacturing binderless materials from bagasse reported much lower mechanical properties (flexural modulus < 2 GPa and flexural strength < 20 MPa) [23,26,50,66]. Meanwhile, the material with the highest water resistance was prepared with a 30 min molding time, giving a WA of 21% and a TS of 9%.…”
Section: Choice Of Best Conditionsmentioning
confidence: 91%
“…There are many tasks to be performed to solve the lack of wood resources, including the renewal of tree species to economic species, increasing the added value of wood, and diversification of wood supply policies, but the effective use of thinned logs or waste wood that is generated in the forestry process has emerged as an urgent issue. To this end, research has been actively conducted on the development of wood composite boards with high productivity and new applications (Iswanto et al, 2020;Jamaludin et al, 2020;Prabuningrum et al, boards (Walker, 1993). Lee and Yoon (1994) fabricated sawdust boards using the Methylene Diphenyl Diisocyanate (MDI) resin, and identified the effects of the specific gravity, mat moisture content, and resin content on the physical and mechanical properties of the boards.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of focus on developing wood-based products including agricultural by-products for structural applications in many of the countries in the Indian sub-continent and South East Asia (Azmi et al, 2019;Hwang and Oh, 2020;Iswanto et al, 2020;Jamaludin et al, 2020;Jose et al, 2022;Khan et al, 2021;Sumardi et al, 2022;Wibowo et al, 2021). Grewia serrulata (GS) trees are found in many locations in India, mainly the Western and Eastern Ghats and regions in the state of Assam, and belong to the Tiliaceae family.…”
Section: Introductionmentioning
confidence: 99%